Pemenuhan Kebutuhan Aman Nyaman Dengan Pemberian Jus Sirsak Terhadap Kadar Asam Urat Pada Lansia Penderita Gout Arthritis - Esther Lenny; Gizka Puti Anggraeni (Sekolah Tinggi Ilmu Kesehatan Sumber Waras, 2024)
Background: Gout or gout arthritis in medical terms, is an inflammatory condition in the joints that results in painful symptoms that feel hot, swollen, and stiff joints due to high uric acid levels. The normal level of uric acid is 3.5-7 mg/dl for men and 2.6-6 mg/dl for women. According to the WHO (World Health Organization), around 355 million people around the world suffer from gout arthritis. In Indonesia, the incidence rate of Gout Arthritis is also high, with a prevalence of 81%. According to data from the Indonesian Ministry of Health in 2018, the number of gout arthritis sufferers in DKI Jakarta reached 6.76%. Gout arthritis often occurs in elderly people due to decreased kidney function and consumption of foods high in purines. One way to lower uric acid levels is to drink soursop juice. Objective: To determine the effect of soursop juice on reducing uric acid levels in elderly people with gout arthritis. Methods: A Case study with descriptive analysis of 2 clients. Results: After an assessment of clients I and II, pain complaints were found, and a diagnosis of chronic pain related to chronic musculoskeletal conditions was raised. The intervention carried out was to administer soursop juice twice a day as much as 200 ml for 7 consecutive days. Client 1 experienced a decrease in uric acid levels from 9.3 mg/dl to 5.7 mg/dl and client 2 experienced a decrease in uric acid levels from 8.6 mg/dl to 5.0 mg/dl. Conclusion: This study shows that there is an effect of soursop juice on reducing uric acid levels in elderly people with gout arthritis in PSBD Budi Bhakti 2 Cengkareng